AUTOMATIC TRAIN DOOR PORTAL SYSTEM USING REGULATED STRAIGHT MOTION FORMULAS - Sri Winar (Universitas Mulia, 2021)
The train station is an important facility. However, the services provided to train passengers are still not optimal. There are still several weaknesses, including the arrival and departure processes of trains that still rely on telephone communication with other station staff. Notification of train arrival will be sent by telephone by the officer at the previous station to the destination station. On receiving notification of arrival, station staff will close the train portal. This process can have a weakness, and namely, if there is the officers' negligence, it can cause an accident. This is due to the absence of an automatic operating system on the railroad crossing portals. Because the manual system must use human labour or operators to operate and open the railroad crossing portals, so that operator error or failure of manual operation of the portal can increase the likelihood of a train accident occurring at the crossing portal, the above problems can be overcome by implementing an automatic portal closure system. With an automatic portal system, the portal will automatically close if a train passes through the crossing.